The Role of Patient Satisfaction as Mediators on the Influence of People, Waiting Time, and Price Fairness on Revisit Intention in A Clinic, Bekasi - Briesha Aurevella Putri Satria; Innocentius Bernarto; Syifa Naira Yudianto; Emmanuelle Jocelyn Handoyo; Alya Nadira (ProBisnis : Jurnal Manajemen, 2025)
This study examines the influence of healthcare professionals (people), waiting time, and price fairness on patient satisfaction and revisit intention at Beauty Clinic A in Bekasi. Using a quantitative, cross-sectional survey approach, data were collected from 141 patients and analyzed using Structural Equation Modeling (SEM) with SmartPLS. The results show that all three variables people, waiting time, and price fairness positively and significantly affect patient satisfaction. Furthermore, patient satisfaction strongly predicts revisit intention, functioning as an effective mediating variable between service quality factors and behavioral outcomes. The model demonstrates strong explanatory power, with 91.4% of the variance in patient satisfaction and 85.2% in revisit intention explained by the tested variables. IPMA results indicate that people, price fairness, and patient satisfaction fall into the high-importance but low-performance quadrant, suggesting the need for managerial prioritization. Overall, the study highlights that professional competence, efficient waiting times, and fair pricing are essential to enhancing satisfaction and encouraging patient loyalty in aesthetic healthcare settings.